Mission as humanisation in the life and work of Bishop Joseph Shanahan : theological evaluation of an intercultural encounter in South-East Nigeria - Oranusi, Thaddeus C. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.